Social Return on Investment (SROI) to Assess the Impacts of Tourism: A Case Study. (February 2021) - Ariza-Montes, Antonio; Sianes, Antonio; Fernández-Rodríguez, Vicente; López-Martín, Carmen; Ruíz-Lozano, Mercedes; Tirado-Valencia, Pilar
This article contributes to the debate on the social and economic impacts generated by tourism activities using a methodology that is still insufficiently explored in the field of tourism and the impacts that this causes: social return on investment (SROI). Using the analysis of a case as a guiding thread, this article shows how the application of this methodology allows one to know in depth the social value that an emblematic palace (one of the main tourist attractions of a city in the south of Spain that was designated as a United Nations Educational, Scientific, and Cultural Organization [UNESCO] World Heritage Site) brings, the changes experienced by the interest groups that interact with it, and the theory of change that promotes the very existence of the palace. Its results and conclusions can also inform policies and strategies of these other actors related to the intervention.